1987
DOI: 10.1111/j.1476-5381.1987.tb11367.x
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐aggregating properties of vascular endothelium: interactions between prostacyclin and nitric oxide

Abstract: 1 The interactions between endothelium-derived nitric oxide (NO) and prostacyclin as inhibitors of platelet aggregation were examined. 2 Porcine aortic endothelial cells treated with indomethacin and stimulated with bradykinin (10-100 nM) released NO in quantities sufficient to account for the inhibition of platelet aggregation attributed to endothelium-derived relaxing factor (EDRF). 3 In the absence of indomethacin, stimulation of the cells with bradykinin (1-3 nM) released small amounts of prostacyclin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
466
1
14

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,082 publications
(491 citation statements)
references
References 17 publications
10
466
1
14
Order By: Relevance
“…A synergistic antiaggregatory e ect of PGI 2 and NO has been originally described in human platelets: low doses of both compounds inhibit aggregation and induce disaggregation of human platelets, while either PGI 2 or NO alone at the same dose are ine ective (Radomski et al, 1987).…”
Section: Discussionmentioning
confidence: 93%
“…A synergistic antiaggregatory e ect of PGI 2 and NO has been originally described in human platelets: low doses of both compounds inhibit aggregation and induce disaggregation of human platelets, while either PGI 2 or NO alone at the same dose are ine ective (Radomski et al, 1987).…”
Section: Discussionmentioning
confidence: 93%
“…Pober et al [23] have also observed that IFN-␥-induced changes were slower and quantitatively smaller than those observed with interleukin-1␤ and TNF-␣. More recently, NO has been recognized as yet another important molecule that inhibits homotypic platelet aggregation [32], as well as decreases platelet adhesion to EC [24]. To validate the role of NO in PMN-EC adhesion, we added SNAP, a S-nitrosothiol derivative and a stable NO donor [25], to the PMN-EC co-culture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PGI 2 also stimulates the release of EDRF [28]. In addition, NO which accounts for the actions of EDRF [29], potentiates anti-aggregatory properties of PGI 2 ; they both can prevent platelet aggregation together at concentrations which on their own too low to inhibit aggregation [30,31]. NO also inhibits platelet adhesion to the vascular endothelium which contributes to nonthrombogenicity of endothelial cell [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…NO also inhibits platelet adhesion to the vascular endothelium which contributes to nonthrombogenicity of endothelial cell [32][33][34]. The ability of the EE to produce these antithrombotic factors plays an important role in preventing thrombus formation in the cardiac chambers [30,35]. The NO also are involved on atrial fibrillation associated with endothelial dysfunction [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation